Characterization of mouse spinal cord vascular network by means of synchrotron radiation X-ray phase contrast tomography. Issue 12 (December 2016) - Massimi, Lorenzo; Fratini, Michela; Bukreeva, Inna; Brun, Francesco; Mittone, Alberto; Campi, Gaetano; Spanò, Raffaele; Mastrogiacomo, Milena; de Rosbo, Nicole Kerlero; Bravin, Alberto; Uccelli, Antonio; Cedola, Alessia
Highlights: Vascular and neuronal networks in ex vivo mouse spinal cord was imaged using XPCT. Intensity-based segmentation method was applied to spinal cord vascular network. Detection of the vascular changed in the healthy and diseased case is discussed. Abstract: High resolution Synchrotron-based X-ray Phase Contrast Tomography (XPCT) allows the simultaneous detection of three dimensional neuronal and vascular networks without using contrast agents or invasive casting preparation. We show and discuss the different features observed in reconstructed XPCT volumes of the ex vivo mouse spinal cord in the lumbo-sacral region, including motor neurons and blood vessels. We report the application of an intensity-based segmentation method to detect and quantitatively characterize the modification in the vascular networks in terms of reduction in experimental visibility. In particular, we apply our approach to the case of the experimental autoimmune encephalomyelitis (EAE), i.e. human multiple sclerosis animal model.